Exchange Differences in Polish and International Accounting Law - A Comparative Analysis - Obrzeżgiewicz , Dawid (Studia Oeconomica Posnaniensia, 2014)
This article presents and compares solutions for accounting transactions in foreign currencies. It analyses Polish and international legal acts relating to exchange differences, using the comparative analysis method. Comparisons were made in three specific areas: valuation of foreign currency transactions, recognition of exchange differences in the financial statements, and conversion of the financial data of foreign enterprises for the purpose of preparing consolidated financial statements. The study confirmed a significant harmonization of Polish accounting law with International Accounting Standards. The differences between Polish and international accounting laws which were identified in the analyses related to very specific legal solutions and did not affect the settlement recognized in financial statements.